2014
DOI: 10.2119/molmed.2014.00059
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib Antagonizes Multidrug Resistance-Associated Protein 1-Mediated Multidrug Resistance by Inhibiting Its Transport Function

Abstract: Lapatinib, a tyrosine kinase inhibitor, is used in the treatment of advanced or metastatic breast cancer overexpressing human epidermal receptor 2 (HER2). Lapatinib can modulate the function of ATP-binding cassette (ABC) transporters (ABCB1 and ABCG2), which are the major mechanism responsible for multidrug resistance (MDR) in cancer. In this study, we investigated the effect of lapatinib on multidrug resistance-associated protein 1 (MRP1 [ABCC1]), MRP2 (ABCC2), MRP4 (ABCC4) and lung relative resistance protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Furthermore, the authors showed that administration of 5 μM of ibrutinib did not alter MRP1 expression. Finally, combination experiments in nude mice xenografts with vincristine showed a synergistic effect on tumor growth, as this was already found for lapatinib …”
Section: Pharmacological and Experimental Drugs And Synthetic Analogssupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, the authors showed that administration of 5 μM of ibrutinib did not alter MRP1 expression. Finally, combination experiments in nude mice xenografts with vincristine showed a synergistic effect on tumor growth, as this was already found for lapatinib …”
Section: Pharmacological and Experimental Drugs And Synthetic Analogssupporting
confidence: 69%
“…With respect to MRP1 inhibition, Ma et al. found similar results . Using the doxorubicin‐selected human epidermoid carcinoma cell line C‐A120, lapatinib (Figure ) reversed doxorubicin and vincristine resistance partially at 2.5 μM, in comparable magnitude to the used standard inhibitor MK571.…”
Section: Pharmacological and Experimental Drugs And Synthetic Analogsmentioning
confidence: 73%
“…Previous studies have reported that several TKIs, including lapatinib, erlotinib, apatinib and afatinib, were able to modulate the MDR phenotype mediated by ABC transporters and encouraged evaluations of the potential of these TKIs to circumvent the anticancer drug resistance in clinical trials. 18, 19, 20, 21, 22, 23 …”
Section: Introductionmentioning
confidence: 99%
“…Lapatinib, which is primarily a tyrosine kinase inhibitor with some effect on inhibiting ABCG2-mediated efflux, has been well-studied with its potential to reverse MDR. (16,32,46) Lapatinib is currently the only compound affecting ABCG2 activity that has been examined in phase II clinical trial for recurrent ovarian cancer. (16) However, the trial was canceled due to substantial adverse hematologic events and no observed benefit.…”
Section: Discussionmentioning
confidence: 99%